2005
DOI: 10.1080/10473289.2005.10464777
|View full text |Cite
|
Sign up to set email alerts
|

Incinerating Volatile Organic Compounds with Ferrospinel Catalyst MnFe2O4: An Example with Isopropyl Alcohol

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…If no CuFe 2 O 4 , the IPA combustion started at about 120 • C, which is much higher than in the case of CuFe 2 O 4 presence. This is consistent with the MnFe 2 O 4 catalyst on IPA combustion [11].…”
Section: Blank Testsupporting
confidence: 89%
See 1 more Smart Citation
“…If no CuFe 2 O 4 , the IPA combustion started at about 120 • C, which is much higher than in the case of CuFe 2 O 4 presence. This is consistent with the MnFe 2 O 4 catalyst on IPA combustion [11].…”
Section: Blank Testsupporting
confidence: 89%
“…It is a relatively cheap catalyst for replacing those of precious metal catalysts. Our previous work showed that hydrothermal synthesized manganese ferrite (MnFe 2 O 4 ) could convert IPA into CO 2 at space velocity of 24,000 h −1 , oxygen content 21%, 1700 ppm IPA, and at reaction temperature of 200 • C [11]. Although copper ferrite has superior catalytic activity [12][13][14], its effect on the thermal decomposition of IPA has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The formation equation of this magnetic iron oxide from hydrothermally ferrite process could be expressed as Eq. (1) [23,28]:…”
Section: Introductionmentioning
confidence: 99%
“…Those precipitated ferrospinels are magnetic and can be easily separated from the wastewater by a magnetic field. Additionally, the sludge generated from the FP can be recycled as magnetic material or a catalyst (Lou and Tu 2005;Huang and Lou 2007). Therefore, the FP has significant potential for treating wastewater.…”
Section: Introductionmentioning
confidence: 99%